Evaluasi Program Integrated Farming System Berbasis Jagung Kabupaten Karawang: INDONESIA - Irwansyah, Wahyu; Purnomo, Sulistyo Sidik; Wulandari, Yeni Sari (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
The integrated agriculture program is the development of an agricultural system, combining livestock and agricultural activities that are mutually sustainable. The corn-based integrated farming system program in Karawang Regency was formed to prosper the community. To see the course of the program in achieving its goals, an evaluation is needed to identify the implementation and results of the program for the community. The research methods used are qualitative and quantitative methods presented in descriptive form. The research resource persons were farmer groups receiving assistance for the corn-based integrated farming system program in Karawang Regency. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis techniques use qualitative data analysis model Miles and Huberman (1984) flow model, quantitative data analysis includes calculations of receipts, total costs, and revenues. The results showed that the implementation of the program was stopped, there were obstacles faced by farmer groups that hindered the achievement of program objectives. The economic impact of the program does not create changes to increase revenue. The impact of the integrated farming system program on the environment, technically agricultural waste is used by farmers, the social impact of the program can provide new experiences for farmers, especially intensive livestock management